EXPRESSION OF HUMAN ERYTHROPOIETIN GENE IN HELA CELLS - U. TIWARI; K. AGARWAL; A. RAI; N. RAI; P. PAL (International Journal of Pharma and Bio Sciences, 2013)
The cloned human erythropoietin (pSin.epo.hu) gene in pSin vector was transfected in HeLa cells. The protein expression was assayed by immuno assay, SDS-PAGE and western blotting. The cells were found to express the protein with development of purple color precipitate in Immunoperoxidase test. Intense purple coloration of cells was observed in HeLa cells transfected with pSin.epo.hu. The vector alone and untransfected healthy cells failed to show any coloration confirmed no expression of proteins. By SDS-PAGE and western blotting, the expressed erythropoietin (34 kDa) was confirmed.